Beveridge Plan (postcard) - Jones, W.
1944-02-21 1944 1940s 2 pages POST CARD THE ADDRESS TO BE WRITTEN ON THIS SIDE SLOUGH 10-AM 21 FEB 1944 BUCKS. Mr William Murdoch Adamson, (Cannock Stafford) [House of Commons] 20 Woodcombe Cres SE23 Westminster 126/TG/377/1/1/106